Temporary mess (making a difference for teens) a guidance activity resource book - Jara, Lito S. (Quezon City New Day Pub., 1998)
Purpose: "Temporary Mess (Making a difference for teens) is a guidance activity book designed to provide counselors with activities aimed at helping our high school young people understand and know themselves better, and process the experiences they go through during this period."
Contents: Adolescence. Peer pressure. Pride. Teen emotions. Relationships. Teenage problems. Reference notes. Appendices.
UCWS-3187g donated by Ma. Theresa D. Ujano-Batangan
Keywords: Home room guidance -- Philippines -- Handbooks, manuals, etc; Counseling in secondary education -- Philippines -- Handbooks, manuals, etc; Teenagers -- Counseling of -- Philippines -- Handbooks, manuals, etc